METHODS DEMONSTRATION AND GROUP DICUSSION METHODS MATHEMATICAL LEARNING DISCUSSION OF CLASS IV IN PAKAM LUBUK LESSON YEAR 2019/2020 - Alexander Samosir; Salim Efendi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2020)
This study aims to determine the use of demonstration methods and group discussions to compare the mathematics learning outcomes of students whose learning uses demonstration methods and group discussions in class V in Lubuk Pakam. This type of research is comparative research. The population in this study were all class V students in Lubuk Pakam, amounting to 2 classes. Sampling was done by random sampling technique. The sample in this study were class VA and VB, totaling 40 students. The data analysis technique used is the t test.The results showed that the completeness of KKM 70 was 74.77% of the 27 students in Cycle I. In Cycle II, students who reached KKM 70 increased by 85.19% with a class average score of 82.59.From the data analysis with t test at the significance level Î± = 0.05 and dk = 60, it is obtained tcount (2.914) <ttable (2.000) so that Ho is rejected and Ha is accepted. From the statistical test it can be concluded that there are differences in mathematics learning outcomes in the two-grade class V building subject, where learning using the group discussion method with the demonstration method can improve mathematics learning outcomes in Lubuk Pakam.So, it can be concluded that learning using demonstration methods and group discussions can improve student learning outcomes in Mathematics.